ON THE RELATION OF THE CATALYTIC ACTIVITY OF THE BLOOD TO THE NUMBER OF RED BLOOD CELLS IN HEALTH, AND TO THE NUMBER OF WHITE BLOOD CELLS AND THE BODY TEMPERATURE IN PERITONITIS - Winternitz, M. C. (The Rockefeller University Press, 1910)
The catalytic activity of the blood of normal rabbits varies almost directly with the volume and number of red blood cells. This explains to a certain extent at least why animals of the same general degree of nutrition, and of the same litter, should have about the same activity since they are likely to have the same number of red blood cells, and why healthy large animals should read high while small poorly nourished ones should read low. Accompanying the hyperpyrexia resulting from puncture of the corpus striatum of a rabbit's brain, there is no change in either the catalytic activity of the blood or the white blood count. In experimentally produced peritonitis, the catalytic activity of the blood always rises, and is, therefore, absolutely independent of body temperature and white blood cells since one or both of these may rise, fall or remain stationary while the catalytic action increases.